A novel localised authentication scheme in IEEE 802.11 based Wireless Mesh Networks. (22nd February 2008) - Lin, Xiaodong; Ling, Xinhua; Zhu, Haojin; Ho, Pin-Han, Xuemin Sherman Shen
In the paper, we propose an efficient two-factor localised authentication scheme for inter-domain handover and roaming in IEEE 802.11 based service-oriented wireless mesh networks (WMNs). Some important aspects, such as resource-constraint Mobile Stations (MSs) and the ping-pong movement phenomenon when handover roaming across different hotspots occurs, are considered. An analytic model is developed to investigate the efficiency of the proposed scheme. Numerical results are given to demonstrate the superiority of the proposed scheme in terms of the resultant signalling overhead, power consumption, and authentication latency, compared with the legacy authentication schemes without losing the capability of preserving the system security.